Vitamin K Insufficiency in the Indian Population: Pilot Observational Epidemiology Study - Rama Vaidya; Ashok D B Vaidya; Jayesh Sheth; Shashank Jadhav; Umakant Mahale; Dilip Mehta; Janusz Popko; Vladimir Badmaev; Sidney J Stohs (JMIR Publications, 2022)
BackgroundThe fat-soluble K vitamins K1 and K2 play an essential role in the blood coagulation cascade and are made available predominantly through selective dietary intakes. They are less known for their nonessential roles in a family of vitamin K-dependent proteins that promote various functions of organs and systems in the body. A lack of vitamin K can characterize vitamin and nutritional element insufficiency, which is different from a clinically apparent vitamin deficiency. ObjectiveThis epidemiological study evaluated the nutritional status of vitamin K in a sample of the Indian population and vitamin K content in staple Indian foods. MethodsSerum levels of vitamin K1 and vitamin K2 in the form of menaquinone-7 (MK-7) were assessed via high-performance liquid chromatography coupled with fluorescence detection in 209 patients with type 2 diabetes, 50 healthy volunteers, and common staple foods in India. ResultsAfter comparing populations with high and low serum vitamin K levels from various geographical regions, our results indicated that the sample of healthy Indian individuals and the sample of Indian patients with type 2 diabetes had low (insufficient) levels of vitamin K2 (MK-7; range 0.3-0.4 ng/mL). No significant differences existed in vitamin K1-related and MK-7-related values between healthy male and female subjects, between male and female subjects with diabetes, and between the healthy sample and the sample of patients with diabetes. The staple, commonly consumed Indian foods that were tested in this study had undetectable levels of vitamin K2, while levels of vitamin K1 varied widely (range 0-37 µg/100 g). ConclusionsBased on our sample's low serum levels of vitamin K2 (MK-7) as well as the low levels of vitamin K2 in their typical diet, we propose that the general Indian population could benefit from the consumption of vitamin K2 in the form of MK-7 supplements. Trial RegistrationClinical Trials Registry - India CTRI/2019/05/014246; http://ctri.nic.in/Clinicaltrials/showallp.php?mid1=21660&EncHid=&userName=014246; Clinical Trials Registry - India CTRI/2019/03/018278; http://ctri.nic.in/Clinicaltrials/showallp.php?mid1=32349&EncHid=&userName=018278